Cardiac-cerebral-renal associations in pediatric traumatic brain injury: Preliminary findings. (June 2020) - Lele, Abhijit V.; Alunpipatthanachai, Bhunyawee; Clark-Bell, Crystalyn; Watanitanon, Arraya; Min Xu, M.; Anne Moore, R.V.T.; Zimmerman, Jerry J.; Portman, Michael A.; Chesnut, Randall M.; Vavilala, Monica S.
Highlights: In children with isolated traumatic brain injury, elevation in troponin (cTnI) is common. Elevated cTnI occurs across all age groups, in both sexes and regardless of lesion type, and across injury severity. Age-adjusted tachycardia may be a clinical indicator of myocardial injury. Abstract: Objective: The clinical epidemiology of organ outcomes in pediatric traumatic brain injury (TBI) has not been examined. We describe associated markers of cerebral, cardiac and renal injury after pediatric TBI. Design: Prospective observational study. Patients: Children 0–18 years who were hospitalized with TBI. Measurements: Measures of myocardial (at least one elevated plasma troponin [cTnI] ≥ 0.4 ng/ml) and multiorgan (hemodynamic variables, cerebral perfusion, and renal) function were examined within the first ten days of hospital admission and within 24 h of each other. Main Results: Data from 28 children who were 11[IQR 10.3] years, male (64.3%), with isolated TBI (67.9%), injury severity score (ISS) 25[10], and admission Glasgow coma score (GCS) 11[9] were examined. Overall, 50% (14 children) had elevated cTnI, including those with isolated TBI (57.9%; 11/19), polytrauma (33.3%; 3/9), mild TBI (57.1% 8/14), and severe TBI (42.9%; 6/11). Elevated cTnI occurred within the first six days of admission and across all age groups, in both sexes, and regardless of TBI lesion type, GCS, and ISS. Age-adjusted admission tachycardia was associated with cTnI elevation (AUC 0.82; p < 0.001). Reduced urine output occurred more commonly in patients with isolated TBI (27.3% elevated cTnI vs. 0% normal cTnI). Conclusions: Myocardial injury commonly occurs during the first six days after pediatric TBI irrespective of injury severity, age, sex, TBI lesion type, or polytrauma. Age-adjusted tachycardia may be a clinical indicator of myocardial injury, and elevated troponin may be associated with cardio-cerebro-renal dysfunction.